1997
DOI: 10.1002/(sici)1099-1379(199701)18:1<83::aid-job779>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Process and outcome: gender differences in the assessment of justice

Abstract: SummaryWe studied the importance that women and men place on distributive and procedural justice. The relationship between distributive justice and several organizational outcomes (e.g. commitment, intent to stay) was stronger for men than women. The relationship between procedural justice and those same outcomes, however, was stronger among women than men. The relation of our ®ndings in justice perceptions are related to other research on gender dierences in interpersonal styles and perceptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
245
8
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(267 citation statements)
references
References 47 publications
9
245
8
5
Order By: Relevance
“…Subsequently, based on a thorough literature review and in-depth interviews, we identified a larger number of company-and customerrelated characteristics and, drawing on justice theory, selected those most likely to influence a complainant's perception of his/her outcome-to-input ratio or of the company's outcome-toinput ratio related to the exchange between complainant and company. The selection of these variables was further confirmed by previous work in other contexts that also examines these characteristics on the basis of justice theory (e.g., Hunt and Kernan 1991;Raimondo, Miceli, and Costabile 2008;Sweeney and McFarlin 1997).…”
Section: Homburg / Fürst / Koschate On the Importance Of Complaint Hamentioning
confidence: 98%
“…Subsequently, based on a thorough literature review and in-depth interviews, we identified a larger number of company-and customerrelated characteristics and, drawing on justice theory, selected those most likely to influence a complainant's perception of his/her outcome-to-input ratio or of the company's outcome-toinput ratio related to the exchange between complainant and company. The selection of these variables was further confirmed by previous work in other contexts that also examines these characteristics on the basis of justice theory (e.g., Hunt and Kernan 1991;Raimondo, Miceli, and Costabile 2008;Sweeney and McFarlin 1997).…”
Section: Homburg / Fürst / Koschate On the Importance Of Complaint Hamentioning
confidence: 98%
“…Çalışanla-rın çalıştıkları organizasyonun çalışanlara her türlü konuda adil olması konusundaki algıları başta işte kalma kararları olmak üzere pek çok kararlarına temel teşkil edebilmektedir (Sweeney ve McFarlin, 1997).…”
Section: İşten Ayrılma Niyetiunclassified
“…(Folger ve Konovsky, 1989;Cropanzano ve Folger, 1991;Cropanzano ve Randall, 1993;Sweeney ve McFarlin, 1997). Dağıtım adaleti gibi bireysel beklentilerle önemli ilintisi olan dengeler çalışanların işte kalma kararında önemli bir etken olarak algılanabilmektedir.…”
Section: Hipotez 1c: çAlışanlarının Etkileşim Adaleti Algısı öRgütselunclassified
“…Following previous researchers (Hrebiniak and Alutto 1972;Angle and Perry 1983;Mathieu and Zajac 1990;Steinhaus and Perry 1996;Balfour and Weschler 1996;Sweeney and McFarlin 1997), six personal variables (gender, marital status, race, educational level, job tenure, and organizational tenure) were statistically controlled to reduce the possibility of spurious relationships based on unmeasured variables. Since gender, marital status, race, educational level were categorical in nature, these variables were initially dummycoded.…”
Section: Methods Of Analyzesmentioning
confidence: 99%